Relacja nadawczo-odbiorcza w dawnym języku prawnym (na materiale "Zwierciadła Saskiego" Pawła Szczerbica z XVI w.) = A transcription and reception relation in the former legal language (on the material of the "Saskie Mirror" by Paweł Szczerbic from the 16th century) - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the study is to characterize the relation between the sender and the receiver in the former legal language from the perspective of pragma- and sociolinguistics. The research material is the "Saskie Mirror" by Paweł Szczerbica from 1581. The basic concepts and tools of analysis were taken from the methodological proposal by S. Borawski. The article examines the relationship between text as a pattern of linguistic behaviour and transformations occurring in the life of the community that result from ever-changing social needs.
Keywords: relacja nadawczo-odbiorcza; wzory zachowań językowych; język prawny; wspólnota komunikatywna determinowana prawnie; "Zwierciadło Saskie"; Szczerbic, Paweł (1552-1609); 16 w.; transcription and reception relation; patterns of linguistic behaviour; legal language; legally determined communicative community; "Saskie Mirror"; 16th century